A role for nonsense-mediated mRNA decay in plants: pathogen responses are induced in Arabidopsis thaliana NMD mutants. - Samantha Rayson; Luis Arciga-Reyes; Lucie Wootton; Marta De Torres Zabala; William Truman; Neil Graham; Murray Grant; Brendan Davies (PLoS ONE)
Nonsense-mediated mRNA decay (NMD) is a conserved mechanism that targets aberrant mRNAs for destruction. NMD has also been found to regulate the expression of large numbers of genes in diverse organisms, although the biological role for this is unclear and few evolutionarily conserved targets have been identified. Expression analyses of three Arabidopsis thaliana lines deficient in NMD reveal that the vast majority of NMD-targeted transcripts are associated with response to pathogens. Congruently, NMD mutants, in which these transcripts are elevated, confer partial resistance to Pseudomonas syringae. These findings suggest a biological rationale for the regulation of gene expression by NMD in plants and suggest that manipulation of NMD could offer a new approach for crop protection. Amongst the few non-pathogen responsive NMD-targeted genes, one potential NMD targeted signal, the evolutionarily conserved upstream open reading frame (CuORF), was found to be hugely over-represented, raising the possibility that this feature could be used to target specific physiological mRNAs for control by NMD.